ELECTRONIC COMMERCE BASED MARKETING STRATEGY FOR UMKM IN TANGGAMUS WITH ENTERPRISE ARCHITECTURE PLANNING APPROACH AND SWOT ANALYSIS - Dewi, Nirmala; Nurphi, Meiria; Noorica, Fuji Wara (Jurnal TAM (Technology Acceptance Model), 2024)
This study aims to design an Electronic Commerce (e-commerce)-based marketing strategy for Micro, Small, and Medium Enterprises (MSMEs) in Tanggamus Regency using the Enterprise Architecture Planning (EAP) approach and SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis. The EAP approach is used to develop an integrated and systematic business architecture to support the implementation of e-commerce. Meanwhile, SWOT analysis is applied to identify internal and external factors that influence the success of the marketing strategy. The results of the study indicate that the main strength of MSMEs in Tanggamus is the diversity of local products that have the potential to be marketed digitally. The weaknesses found include limited technological knowledge and lack of supporting infrastructure. Great opportunities are seen in the increasing internet penetration and government support for the digitalization of MSMEs, while the main threats come from global market competition and data security issues. Based on the EAP approach, this study produces an architectural plan that includes business process integration, information system development, and training strategies for MSME actors. By utilizing strengths and opportunities, and overcoming weaknesses and threats, the implementation of this e-commerce-based marketing strategy is expected to be able to increase the competitiveness of MSMEs in Tanggamus sustainably.